The Influence of Corporate Social Responsibility on Product Loyalty Focuses on the Beverage Firms: An Ordinary Least Square Approach - Arlyn S Feliciano; Xavier Lawrence D. Mendoza; Jerico B. Tadeo; Marilou A Perez; Mary Christine P Villalobos (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
The influence of corporate social responsibility (CSR) on consumer behavior makes it a crucial marketing strategy for businesses. The primary intent of this paper was to investigate the impact of corporate social responsibility perceived performance on the product loyalty of customers towards beverage companies. The researchers employed a descriptive-causal design. This study used purposive sampling and selected 500 participants. The researcher-made survey questionnaires were distributed to the participants through an online survey and analyzed through the ordinary least squares regression model. The findings revealed that the CSR initiatives of beverage companies were somehow visible, signifying that beverage enterprises lack communication strategies to inform the public about their CSR efforts. It was also found that the perceived performance of CSR has a significant effect on the product loyalty of customers. Considerably, product loyalty was significantly related to the perceived performance of CSR. Hence, this study confirmed the stakeholder theory with strong statistical significance. The study recommends that beverage companies should effectively communicate their CSR activities to increase customer awareness, eventually enhancing product loyalty among their customers. Keywords: corporate social responsibility, perceived performance, product loyalty, regression analyses, Philippines